Plasminogen Activator Inhibitor Type-1 (PAI-1) and its Role in Cardiovascular Disease - Nordt, Thomas K.; Peter, Karlheinz; Ruef, Johannes; Kübler, Wolfgang; Bode, Christoph (Thrombosis and Haemostasis, 1999)
Cardiovascular disease is responsible for approximately 50% of total mortality in Europe, the USA and Japan (1). Established risk factors including smoking, hypercholesterolemia, and hypertension explain about half of the incidence of cardiovascular disease only (2). Reduced endogenous fibrinolytic activity secondary to increased plasma activity of plasminogen activator inhibitor type-1 (PAI-1) is now considered as a new cardiovascular risk factor. In this review, evidence is gathered for the notion that PAI-1 constitutes a predictor of cardiovascular disease and also contributes to the development of cardiovascular disease as a pathogenetic factor. The review will focus on experimental studies modulating PAI-1 activity and clinical studies addressing coronary heart disease, myocardial infarction, restenosis after coronary angioplasty, and graft occlusion after coronary artery bypass grafting.
Keywords: Endogenous fibrinolysis; atherogenesis; arteriosclerosis; risk factor